Penilaian Kriteria Green Building Pada Gedung Puskesmas Bantar Kota Tasikmalaya - Sandi Ratih, Septi Putri (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2025)
The government urged to start a national movement to save energy, materials, electricity and water. The application of the green building concept can be done to start this movement. The future health center model must be managed well and be measured by health, economic, ecological and social aspects. Community health center administrators must consider the environment as a basis for every policy formulations also social and aesthetic balance.This research aims to determine the level of implementation of the Green Building in the Bantar Health Center Building, Tasikmalaya City and recommendations to meet the Green Building criteria. The method used in this research is the observative method or observation, interviews and document studies. The analysis result level of the green building implementation was identified as meeting the criteria for environmentally friendly buildings with the GBCI and KKRI greenship guideline standards of 58.24% and